Teachers Performance in Relation to Pupils Academic Achievement in Kabankalan City - Malacapay, Marjon C. (JPAIR Multidisciplinary Research, 2018)
Teacher’s performance in relation to pupils’ academic achievement is a quantitative type of research that utilized the descriptive-correlational design. The study aimed to determine the relationship between teachers’ performance in terms of teaching-learning process, pupils’ outcome, community involvement, and professional growth to their pupils’ academic achievement. The researcher distributed a two-part survey questionnaire to the teachers (n=117) covering their demographic profile, and the four performance indicators, while only the second part was distributed to the observers/raters. The researcher then utilized descriptive and inferential statistics for data analysis. Young female teachers, mostly Teacher-I, between a 1-5 year in service, receiving six to ten thousand Pesos (P6,000-10,000) monthly net income and had 21-30 accumulated training hours dominated the population. Also, findings showed that teachers performed very satisfactory, but pupils only performed satisfactorily in terms of academics. Moreover, the teaching-learning process and pupil’ outcome have significant relationships on teacher’ length of service. A significant difference was only found in rural and urban teacher’ community involvement. Lastly, a significant relationship on pupil’ academic achievement was only found on teacher’ community involvement. Therefore, among the performance indicators, teacher’ community involvement solely affects pupil’ academic performance but they least prioritize it.